THE USE OF VIDEO BLOG TO TEACH SPEAKING OF RECOUNT TEXTS - Yulianti Yulianti; Sudarsono Sudarsono; Endang Susilawati (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2018)
AbstractThe purpose of this research was to investigate the effectiveness of using video blog to teach speaking of recount texts to Year-10 students of SMA Negeri 5 Pontianak in Academic Year 2017/2018. The research was conducted to solve some problems in teaching speaking about recount text. The problems were most students lack of topic consistency, fluency and accuracy during speaking performance. It was a pre-experimental study with a single group pre-test post-test design. The sample was Year -10 students that consisted of 36 students. The data was collected using measurement technique in term of spoken test. Then, this research is analyzed by t-test which the t-test (14.83) were higher than the t-table 36 (1.697) in level 0.05. The data were also analyzed by using Effect Size (ES) to find how effective this medium. The research finding showed that the effect size of the treatment was 2.37 (2.37>0.8). It was categorized as very strong. Therefore, the alternatif hypotheses (Ha) which stated “using video blog is significant to teach speaking of recount texts on the tenth grade students of SMA N 5 Pontianak in academic year 2017/2018” was accepted. Key Words: Video Blog, Recount Text, Speaking.